Micro-scale fracturing mechanisms in coal induced by adsorption of supercritical CO2 - Zhang, Y.; Zhang, Z.; Sarmadivaleh, Mohammad; Lebedev, Maxim; Barifcani, Ahmed; Yu, H.; Iglauer, Stefan (2017)
Coal bed methane production can be assisted by CO2 injection. However, CO2 adsorption in the coal matrix leads to a dramatic reduction in permeability and an associated change in microstructure caused by coal matrix swelling. Furthermore, it has been recently observed that the induced swelling stress fractures the unswelling (mineral) phase in laboratory investigations. However, the failure mechanisms are still not understood, and the way internal swelling stresses are generated is not clear. Thus, in this paper, we propose a new method which combines X-ray microtomography imaging, nanoindentation testing and DEM modelling with which we can predict the rock mechanical performance at micro scale. Indeed we successfully simulated such swelling processes inside a coal sample, including a simulation of the fracture mechanism of the mineral phase, and a quantification of the in-situ von Mises stresses generated by swelling. We conclude that our proposed method is an efficient way for analysis and prediction of coal microfracturing and the associated microscale rock mechanical behavior.